Pengaruh Leverage, Profitabilitas, Struktur Kepemilikan Saham Dan Kompleksitas Perusahaan Terhadap Audit Delay - Novi Eliza; Rachmat Arif (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The study aims to determine the Effect of Leverage, Profitability, Stock Ownership Structure, and Complexity of Company on Audit Delay. The sample selection technique in this study used the purposive sampling method and obtained 26 food and beverage companies listed on the Indonesia Stock Exchange for the period 2018 – 2021. The data analysis used in this study was multiple linear regression analysis using SPSS version 19 software. The results of the study can be concluded that the leverage and profitability of the auditor have a negative and significant effect on audit delay, while stock ownership structure and complexity of company have no effect on audit delay.